PENGETAHUAN TENTANG ISU PENGURANGAN RISIKO BENCANA BERBASIS KOMUNITAS KELOMPOK SIAGA BENCANA DI KECAMATAN PADANG BARAT KOTA PADANG - Tiurmaida Simandalahi* Ahsan** Ari Prasetyadjati*** (The Indonesian Journal of Health Science, 2016)
The issue of disaster management has become a global movement that hasto be done to anticipate the major risks arising from the disaster. The issue ofdisaster management is being developed is the Community-Based Disaster RiskReduction (CBDRR). Target of CBDRR is to activate communities in disaster-proneareas to be able to carry out activities CBDRR. This paper presents an overviewthe knowledge of CDP about the issues of CBDRR in Padang. This research useda descriptive method to quantitative descriptive approach. A sampling method thatused is total population, with 40 respondents CDP of the urban village BelakangTangsi Olo. The results showed than 40 respondents, obtained 37 respondents(92%) have a sufficient knowledge level. Respondents were weak in the parametersof the principle PRBBK especially principles regarding the role and responsibilitiesof government and society, as well as the parameters of the funding. Socializationperiodically through the provision of material and training related CBDRR to theentire CDP is expected to increase the knowledge and understanding of the effortsPRBBK.